Synthesis of Chalcone and Flavanone Compound Using Raw Material of Acetophenone and Benzaldehyde Derivative - Ismiyarto Ismiyarto; Sabirin Matsjeh; Chairil Anwar (Indonesian Journal of Chemistry, 2001)
Synthesis of flavanoid compounds of chalcone and flavanone groups have been conducted. Flavanoid Is one of the group natural products which is mostly found in plants and have been proved to have physiological activity as drug. In this research, chalcone proup compounds that being synthesized are: chalcone, 3,4-dimethoxychalcone, 2'-hidroxy-3,4-dimethoxychalcone where as compound of flavanone group that being synthesized is 3',4'-dimethoxyflavanone. The synthesis of chalcone group are carried out based on Claisen-Schmidt reaction by using raw material of aromatic aldehydes and aromatic ketones. The synthesis in carried out by stirring at the room temperature using alkali solution as catalyst and ethanol as solvent. The synthesis of 3',4'-dimethoxyflanone is made based on the nucleophilic 1,4 addition of the unsaturated α,β ketone. The synthesis is made by refluxing 2'-hydroxy-3,4-dimethoxychalcone in alkali condition for 12 hours. The identification of flavanoid compound is carried out by using spectroscopic IR, GC-MS and 1H-NMR methods. The result of each synthesis chalcone group are follows: chalcone as yellowish solid with m.p= 50 °C and the yield is 83.39%; 3,4-dimethoxychalcone as yellow solid with m.p= 57°C and the yield is 76.00% ; 2'-hydroxy-3,4-dimethoxychalcone as orange solid with m.p= 90 °C and the yield is 74.29%, for 3',4'-dimethoxyflavanone as pale yellow solid with m.p= 80 °C and the yield is 72.00%.